Optimization of Livestock Waste as an Alternative Energy Source and Community Organic Fertilizer in Puuwatu District, Kendari City - Astarika, Rina; Zulkarnain, Deki; Aku, Achmad Selamet; Pagala, Muhammad Amrullah; Yaddi, Yamin; Syamsuddin, Syamsuddin; Rusdin, Muh.; Auza, Fuji Astuty; Asminaya, Nur Santy; Abadi, Musram; Munadi, La Ode Muh.; Sani, La Ode Arsad; Indi, Amiluddin; Sahaba, La Ode; Jabuddin, La Ode (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2024)
Kendari City has a large potential for livestock waste because it has a cattle population of 2,203 heads, placing Puuwatu District as having the largest cattle population, namely 585 heads. This study aims to optimize livestock waste as an alternative energy source and organic fertilizer for the community in Puuwatu District, Kendari City using the Participatory Rapid Appraisal (PRA) approach and the Technology Transfer Approach. The results of the optimization of livestock waste indicate that Puuwatu District has a large enough potential for livestock waste so that further waste treatment is needed